CREATING A TEA SHOP WEBSITE USING MICROSOFT AZURE - Candra, Bambang Adi; Winjaya, Fernando Arga; Widiadi, Muhamad; Firmansyah, Fauzi; Muharam, Rizal, Sunjana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Cloud computing is a set of technologies and infrastructure technologies represented by a holistic consumption model primarily based on utilities. Windows Azure is Microsoft's cloud computing showcase designed to help customers understand the benefits of cloud computing. This article is the arrival of Windows Azure and provides an understanding of the many elements of Azure, especially those that are fully enhanced, especially for those interested in embracing Windows Azure in their corporate IT environment. Cloud computing is affecting many industries including e-learning, healthcare, and e-commerce. We provide highly efficient and affordable online services that provide high economic value. Undoubtedly, there has been a revolution in the world of the Internet and the world of business. A growing number of e-commerce companies are turning to cloud computing for its outstanding practical value. This journal provides an overview of cloud computing in e-commerce and discusses the benefits and challenges of adopting cloud computing in e- commerce. To resolve the conflict between the company's e-commerce activities and resource constraints, the company has implemented an advanced cloud computing service model that addresses the shortage of funds, manpower, and skills needed to operate e-commerce. Solve e-commerce challenges and resource constraints by simulating cloud-based e-commerce applications and building e-commerce application frameworks based on cloud computing environments. Research shows that using a business application model in businesses and their own e-commerce through network resources solves the problem. The cloud-based e-commerce application model enables enterprises to reduce costs through efficient e-commerce operations and solve the problem of enterprises unable to grow their e-commerce business due to lack of resources.